Electrical conductivity test in the evaluation of physiological quality in seeds of Zeyheria tuberculosa - Soto Gonzales, Jose Luis [UNESP]; Valeri, Sergio Valiengo [UNESP] (Univ Austral Chile, Fac Ciencias Forestales, 2011)
The electrical conductivity test is still an excellent tool to evaluate the effect of seeds of various forest and agricultural species and recent studies have been conducted aiming at verifying its application in forest seeds. The objective of this study was to establish a specific methodology to test the electrical conductivity of forest seeds of Zeyheria tuberculosis. Four lots of seeds were used, which were submitted to the germination test, evaluating the percentage of germination, germination speed index and dry mass of seedlings. For the electrical conductivity test, five replicates of 20 seeds installed in three volumes of deionized water (75, 100 and 125 mL) were used and eight periods for seed imbibitions (2, 4, 6, 12, 18, 24, 48 and 72 hour) at 25 degrees C were allowed. The statistical design used was completely random; the comparison of means was performed by Tukey test at 5 % probability. Lot II showed higher germination percentage and speed. The electrical conductivity test allows discrimination of the same batch by the germination test under laboratory conditions. It was possible to separate the seed lot presenting better physiological quality (lot II) from among the other lots. It was recommended the use of 75 or 125 mL of deionized water at a temperature of 25 degrees C to perform the electrical conductivity test.
Keywords: vigor of seeds; Native forest seed; Physiological seed quality